Characterization of Holliday structures in FLP protein-promoted site-specific recombination. - Meyer-Leon, L (1990)
Holliday structures are formed in the course of FLP protein-promoted site-specific recombination. Here, we demonstrate that Holliday structures are formed in reactions involving wild-type substrates and that they are kinetically competent with respect to the overall reaction rate. Together with a previous demonstration of chemical competence (L. Meyer-Leon, L.-C. Huang, S. W. Umlauf, M. M. Cox, and R. B. Inman, Mol. Cell. Biol. 8:3784-3796, 1988), Holliday structures therefore meet all criteria necessary to establish that they are obligate reaction intermediates in FLP-mediated site-specific recombination. In addition, kinetic evidence suggests that two distinct forms of the Holliday intermediate are present in the reaction pathway, interconverted in an isomerization process that is rate limiting at 0 degree C.